(untitled) (Transport systems and technologies, 2019)
Nowadays, the current topic is to ensure the smooth operation of network equipment in the transport industry. In this article reviews the technologies that are used to ensure stability and quality of Internet connection and prove resources needed to physical level of the network, described requirements to net equipment through which users are connected, especially ports configuration, which are used to establish connection via switches. Attention is paid to defence methods of communication lines. For accomplishing the task set for the network it is required to configure a big list of technologies and methods. That list includes such technologies as VLAN, NAT and STP. Firstly, attention is paid to create an adequate network plan. For example, internet-provider has to know the amount of inputs, amount of subnets used, their numeration, count of possible connections. The next step should be in choosing network equipment and topology of connection, location and cable routing, cable type. Topology and structure of the net has to be chosen responsibly, because stability and durability depends on them. The paper gives an example of configuring computer network.